Time Criterion in Islamic Finance: Analytical study in the light of Al-Zarqa's rule of Shariah debts - Al-Suwailem, سامي بن إبراهيم (Journal of King Abdulaziz University: Islamic Economics, 2022)
This article presents the "Time Criterion" for identifying usury-based lending or ribā from trade and relates it to the concepts in economic theory. This criterion implies that the cost of financing cannot exceed the exchange value or utility if both parties were spot. Since the two parties are identical in a loan, the spot exchange will have no economic value; if Time is introduced, the cost of financing must be less than or equal to zero, which is a qard hasan or benevolent loan. The article also presents a mathematical formulation of the criterion which will demonstrate the acceptable range of the cost of financing, in case of an exchange, for both the creditor and the debtor. This formulation shows how Zarqa Rule can integrate with economic theory concepts to produce a unified criterion. The article then explores new dimensions of the relationship between "potential" and "actual" wealth, the role of debt or leverage in this relationship, and its impact on inflation under current circumstances.